2009
DOI: 10.17221/921-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Reaction Products Resulting from Heat-Induced Degradation of Inulin

Abstract: From inulin which had been heated for 30 min at 200°C, four di-d-fructose dianhydrides (DFDAs) were isolated using flash chromatography and final purification by semipreparative HPLC, followed by identification via NMR spectroscopy.and β-d-Fruf-1,2´:2,1´-β-d-Fruf were identified. The yield of the isolated DFDAs varied depending on the DP of the used inulin. Using the isolated DFDAs as reference compounds, quantification of the disaccharides in commercial bakery products via high-performance anion-exchange chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…However, fructose is not the final thermal decomposition product of inulin during roasting, as it continues to break down to generate other substances. A considerable number of previous studies that used inulin, fructose, and amino acids as reactants in the roasting process exist. ,, In the present study, the products DFA I and NF were also identified in roasted chicory root. This result demonstrated that, different from studies that were focused on a limited number of simple components, the formation of DFA I and NF was the dominant thermal reaction during the roasting process of chicory root.…”
Section: Discussionsupporting
confidence: 52%
“…However, fructose is not the final thermal decomposition product of inulin during roasting, as it continues to break down to generate other substances. A considerable number of previous studies that used inulin, fructose, and amino acids as reactants in the roasting process exist. ,, In the present study, the products DFA I and NF were also identified in roasted chicory root. This result demonstrated that, different from studies that were focused on a limited number of simple components, the formation of DFA I and NF was the dominant thermal reaction during the roasting process of chicory root.…”
Section: Discussionsupporting
confidence: 52%
“…Therefore, it can be concluded that pectin gels are more effective in binding water and are more stable to high temperatures, in contrary to inulin. Inulin is composed with long fructose chains, which during thermal treatment are readily decomposed to new products, mainly fructose and di-D-fructose dianhydrides [ 22 , 23 ]. This process accelerates the non-enzymatic browning of dough leading to the formation of Maillard compounds [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%